Pharmacological effects of Artocarpus lakoocha methanol extract on inhibition of squalene synthase and other downstream enzymes of the cholesterol synthesis pathway. (31st December 2022) - Shafaq,; Akhtar, Tasleem; Ishaq, Hafiz Muhammad; Shahzad, Muhammad
Abstract: Context: Artocarpus lakoocha Roxb. (Moraceae) is reported to possess antioxidant, anti-inflammatory, and anti-skin ageing agents. Objective: This study evaluates the pharmacological effects of A. lakoocha leaves methanol extract on enzymes involved in the cholesterol synthesis pathway in high-fat diet-induced hyperlipidemic rats. Materials and methods: Twenty-four male Wistar rats, weighing approximately 180–220 g, were divided into four groups: control, diseased (hyperlipidemic), A. lakoocha leaves extract treated, and simvastatin treated. The rats were fed with high-fat diet for 2 months to induce hyperlipidaemia, afterward, experimental groups received A. lakoocha leaves methanol extract (250 mg/kg) and simvastatin (10 mg/kg) orally until the 89 th day of the experiment, while the diseased group continued to receive high-fat diet along with normal saline. Results: It was found that A. lakoocha extract significantly lowered the serum total cholesterol, triglycerides, and low-density lipoprotein (LDL) levels, while effectively increasing serum high-density lipoprotein (HDL) levels as compared to the diseased group ( p  ≤ 0.05). The mRNA expression levels of squalene synthase and HMG-CoA reductase were found to be effectively down-regulated after the treatment with A. lakoocha leaves extract (17.45 ± 2.48 vs. 31.91 ± 5.292 and 5.85 ± 3.164 vs. 37.37 ± 6.492) and simvastatin (7.148 ± 0.76 vs. 31.91 ± 5.292, and 3.098 ± 2.09 vs. 37.37 ± 6.492) as compared to the diseased group. Discussion and Conclusions: The results suggested that A. lakoocha leaves extract have observable beneficial effects on inhibition of enzymes involved in cholesterol synthesis pathway and improve lipid profile analogous to simvastatin.